Legal aspects of occupational therapy - Dimond, Bridgit. 4 0 16; 5 (Chichester, West Sussex ;;Malden, MA : Wiley-Blackwell, 2010)
Since publication of the original edition in 1996, this book has established itself as an essential text for occupational therapists. It offers an understanding of the law relating to their practice, but is written to be accessible for those who have no prior legal knowledge. The text provides valuable information for occupational therapists employed in health and social services, as well as the law relevant to private practitioners. The book includes chapters on all the main client groups and presents the relevant specialist law. Students and teachers of occupational therapy will find the chapters on professional registration, education, training and research of particular interest. The third edition has been substantially revised to cover significant changes in legislation since the previous version. There is also a brand new chapter on the subject of death and dying. Legal Aspects of Occupational Therapy remains a key resource for the occupational therapy student, practitioner and service manager.--Provided by publisher.
Includes bibliographical references and index.
Keywords: 2 -- 0; 6; 20; 20; 2